Legislative and Bioethical Implications of Informed Consent in the Drafting of the Therapeutic Abortion Protocol - Pérez Dávila, Belú Fiorella (2018)
Therapeutic abortion is a medical practice that has been decriminalized in our country and is currently regulated under a standardized procedure at the national level in the so-called Protocol of Therapeutic Abortion (PAT), requiring the informed consent (IC) of the pregnant woman but without considering the rights of the child. The present paper contains both a bioethical analysis, from a principialistic and personalistic perspective, and a legislative analysis of the IC of the pregnant woman regulated by the PAT as a requirement for the realization of an abortion for therapeutic reasons. It seeks to discern its degree of suitability, both from a bioethical and a legal standpoint.